Dosis de consorcio microbiano y grado de temperatura en la vida útil de una longaniza artesanal - Altamirano Rodríguez, Danny José (2019)
The present investigation was carried out with the objective of determining the dose of microbial consortium (Lactobacillus plantarum, Lactobacillus acidophilos, Bacillus subtilis) and the storage temperature that guarantees the prolongation of the useful life of an artisanal sausage in Chone-Manabí. Three doses of probiotics (a) of 1mL were considered; 5mL; 10mL and two storage temperatures (b) of 6 and 27 ° C, obtaining 6 treatments plus a control. If you applied a Bifactorial A * B + 1 design conducted in a Completely Random Block Design with three repetitions, and the Labuza (3.1)equation to determine the best treatment in life time; As an experimental unit, a portion of sausage of 454 g was used, to which the doses of probiotics established in the treatments were added. Measurements of pH, acidity, humidity and microbial growth values were made to the finished product and, after 15 and 30 days of storage, these physical-chemical and bromatological parameters were processed using the SPSS version 20 program. Most treatments were not presented logarithmic loads greater than those allowed by the INEN 1338: 2012 standard with respect to the microorganisms quantitatively analyzed (Aerobic mesophilic, Escherichia coli, Staphilococcus aureus), identifying the T5 treatment (10mL of microbial consortium - 6 ° C storage temperature) as the best at the microbiological level for presenting greater antimicrobial capacity with a useful life of 63 days; and to the T4 treatment (5ml of microbial consortium - 27 ° C storage temperature) as the best from the statistical point of view.